Formation of chlorine dioxide under laundry bleaching conditions. Issue 4 (1st July 2003) - Gregory, Dean; Carr, Mary; Carlson, Kenneth
Abstract : Chlorite ion is a by-product of chlorine dioxide and is typically present at concentrations ranging from 0.3 to 1.0 mg/L in the finished water of systems using this oxidant in the treatment process. When combined with free chlorine, these two reactive ions have been shown to react to form chlorine dioxide. Chlorine dioxide concentrations formed in tap water (either in the distribution system or during domestic use of tap water, such as laundry bleaching) can off-gas in a home and react with volatile organic compounds associated with new carpets and furniture fabrics, resulting in cat-urine type odors and customer complaints. The objective of this study was to determine if chlorine dioxide is formed when the high concentrations of hypochlorite ion that are used in laundry bleaching operations are contacted with residual chlorite ion that is present in tap water of systems using chlorine dioxide at the treatment plant. If chlorine dioxide is forming under these circumstances, it could be a cause of seemingly random odor complaints periodically received by water utilities using chlorine dioxide. The formation of chlorine dioxide was found to be negligible under simulated laundry bleaching conditions. The key factor in chlorine dioxide formation was found to be pH. When chlorine is added as a base (e.g., sodium hypochlorite), the resulting pH is high enough to suppress chlorine dioxide formation.